PROTOTIPE KURIKULUM MERDEKA BELAJAR MELALUI MEDIA HOTS (HIGHER ORDER THINKING SKILLS) DI MADRASAH IBTIDAIYAH SYEKH MANSHUR PANDEGLANG - Agus Hidayatullah; Desyi Rosita; Aat Royhatudin; Ahmad Hidayat; Arifiani Nailul Fauziyah Rohmah; Angger Putri Mahardini (Almarhalah, 2023)
ABSTRACTThis research is motivated by the existence of learning with methods that are still on, which ensures that learning does not provide choices and opportunities for students to think critically. The purpose of this study is to provide students with choices with critical thinking in order to create learning in accordance with the vision and curriculum of the madrasa. The research method is more of a data collection technique through in-depth observation, and then analyzed with data collection techniques, data presentation and conclusions. The results of this study can be seen from the vision, mission and character values developed in madrasas through values and characters that are very relevant to the independent learning curriculum which of course greatly determines the situation of the madrasa civitas starting from the head, educators, education staff, and students who have worked to work together to make superior and quality madrasas.  Keywords: Independent Learning Curriculum Prototype, HOTS Media (Higher Order Thinking Skills).